THE INFLUENCE OF EMPLOYEE INVOLVEMENT AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH SATISFACTION AS A MODERATION VARIABLE (STUDY OF EMPLOYEE BSI KCP JAKARTA): Direct Influence and Indriect Influence - Firdaus, Adhy (I-Economics, 2023)
Abstract Employee involvement in various work programs and comfort in the work environment has great potential in improving employee work performance due to the emergence of inner and outer satisfaction in the employee. To prove the statement above, this study aims to determine how much influence employee involvement and work environment have on employee performance and indirectly with satisfaction as a moderating variable. This research is a quantitative research using techniques purposive sampling. The research sample consisted of BSI bank employees in Jakarta. The population in this study was 200 BSI KCP Jakarta bank employees with a minimum criteria of having worked for 1 year using a questionnaire and data were analyzed usingPath Anaylisis. Keywords: "Employee Performance, Employee Engagement, Work Environment, Satisfaction"